Algunos aspectos generales de la producción de yuca y extracción de almidón en Modomo (Cauca) - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1979)
A brief analysis is made of the general aspects of cassava cultivation and soil types in Mondomo, state of Cauca (Colombia). Emphasis is placed on bitter starch production, with 25 starch factories working throughout the yr. These generally operate with 2 permanent workers and are classified as small, medium and large (4000, 7000 and 10,000 kg of cassava/wk, resp). The production of starch varies according to the var. and age (cassava 10 mo old does not have a high starch content, while that 16-18 mo old does). In general, 125 kg of cassava produce 12.5 kg of starch slurry. Buyers from Santander de Quilichao grant credit to mills, thus assuring their market; in Mondomo, 7 middlemen buy the greater than part (86.6 percent) of the starch produced.(CIAT)